Tissue Sodium Accumulation: Pathophysiology and Clinical Implications - Endre Sulyok; Bálint Farkas; Bernadett Nagy; Ákos Várnagy; Kálmán Kovács; József Bódis (MDPI AG, 2022)
Excessive sodium intake has been well established as a risk factor for the development and progression of cardiovascular and renal diseases. Its adverse effects are achieved by renal sodium retention and related volume expansion and by inducing low-grade inflammation and oxidative stress (OS) in the target tissues. This review presents the recent concept of nonosmotic sodium storage in the skin interstitium, the subsequent dissociation of sodium and volume homeostasis, and the cellular response to the increased tissue sodium concentration. Furthermore, data are shown on the sodium barrier and buffering potential of the endothelial glycocalyx that may protect the functional integrity of the endothelium when it is challenged by an increased sodium load. Finally, examples will be given of the involvement of oxygen free radicals (OFR) in sodium-induced tissue damage, and some clinical entities will be mentioned that are causally associated with sodium/volume retention and OS.